Gertrude Abercrombie. - Burleigh, Paula (Artforum International, 2025)
The article examines Gertrude Abercrombie's surreal paintings, focusing on her eerie, anthropomorphic trees and symbolic landscapes that reflect a mysterious, more-than-human world. Topics include her unique visual language, personal mythology shaped by Chicago's cultural scene; and the interplay between nature and identity in her work.